Differences in the level of cognitive abilities among athletes who prefer different sports games - Mavric, F.; Milic, V.; Memic, M.; Preljevic, A. (FIS communications in Physical Education, Sport and Recreation, 2016)
The research was conducted on a sample of 200 male respondents, ages 16 to 19 years who prefer different sports games (football, volleyball, handball and basketball). The research was conducted in order to identify statistically significant differences in the level of cognitive abilities between athletes who prefer different sports games. The KOG-3 battery that was applied for the assessment of the cognitive abilities is designed to measure the level of general cognitive abilities and it consists of the three following tests: IT-1 test for assessing the efficiency of the perceptual processor, AL-4 test for assessing the efficiency of the serial processor and the S-1 test for assessing the efficiency of the parallel processor, with an aim of determining statistically significant differences between athletes of different sports orientation. The results of the discriminant analysis of the cognitive variables showed that the tested athletes are statically significantly different in relation to their preferred sports game.